Comparison of retina specialist preferences regarding spectral-domain and swept-source optical coherence tomography angiography - Su GL (Dove Medical Press, 2017)
Grace L Su,1 Douglas M Baughman,2 Qinqin Zhang,3 Kasra Rezaei,2 Aaron Y Lee,2 Cecilia S Lee2 1Lewis Katz School of Medicine, Temple University, Philadelphia, PA, 2Department of Ophthalmology, 3Department of Bioengineering, University of Washington, Seattle, WA, USA Purpose: The aim of this study was to compare physician preferences regarding the commercially available spectral-domain (SD) optical coherence tomography angiography (OCTA) and swept-source (SS) OCTA prototype device.Design: Comparative analysis of diagnostic instruments was performed.Patients and methods: Subjects at the University of Washington Eye Institute and Harborview Medical Center were prospectively recruited and imaged with the Zeiss SD OCTA (HD-5000, Angioplex) and Zeiss SS OCTA (Plex Elite, Everest) devices on the same day. The study included 10 eyes from 10 subjects diagnosed with a retinal/choroidal disease. Deidentified images were compiled into a survey and sent to retina specialists in various countries. The survey presented masked SD and SS images of each eye for each retinal sublayer side by side. Respondents were asked about their image preference and impact on clinical management. A priori and post hoc preferences for SD vs SS were collected.Results: Fifty-four retina specialists responded to the survey. Median years in practice was 3.00 (interquartile range [IQR] 1.50–17.00). At baseline, 23 (48%) physicians owned an OCTA machine. The majority of physician responses showed a preference for the SS over SD OCTA, independent of the retinal pathology shown (n=454 overall responses, 74%). Nevertheless, the majority indicated that both SD and SS would be equally valuable in informing clinical decisions (n=374 overall responses, 61%).Conclusion: These findings indicate that the majority of retina specialists surveyed prefer SS over SD OCTA based on image quality, regardless of the retinal pathology shown. Regarding the clinical utility of each modality, the majority of physicians perceive SD and SS as equally effective. Keywords: swept-source optical coherence tomography angiography, spectral-domain optical coherence tomography angiography, physician preference